2009
DOI: 10.1002/elps.200800495
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative analysis of letrozole, fluoxetine and their metabolites in biological and environmental samples by MEKC

Abstract: A micellar electrokinetic chromatographic method has been developed to analyze biological (human serum, saliva and urine) and environmental samples (three different water samples) for letrozole (LE), fluoxetine and their main metabolites. For this purpose a 20 mM borate buffer (pH 9.5) containing 20 mM SDS and 12% v:v 2-propanol was used as the background electrolyte. The samples were hydrodynamically injected for 6 s, separated in a fused-silica capillary at 25 kV and 50 degrees C and detected at 230 nm. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…At the beginning of determinations we have selected the type of background electrolyte (BGE) by checking the electrophoretic behavior of the analytes using an acidic BGE -phosphoric acid 25 mM and a basic BGE -25 mM borax. After our prelimary results we selected a 25 mM borax (pH 9.3) as BGE also taking in consideration previous electrophoretic studies [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of determinations we have selected the type of background electrolyte (BGE) by checking the electrophoretic behavior of the analytes using an acidic BGE -phosphoric acid 25 mM and a basic BGE -25 mM borax. After our prelimary results we selected a 25 mM borax (pH 9.3) as BGE also taking in consideration previous electrophoretic studies [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Several capillary electrophoretic methods have been reported for determination of AIs in combination with other compounds, mainly micellar electrokinetic capillary chromatographic (MEKC) [17][18][19][20]. So far, there is no published electrophoretic method for the simultaneous determination of all three AIs selected in this research.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we choose to start with a 25 mM phosphate buffer, an acidic background electrolyte (BGE), but the electrophoretic signal of the substance was difficult to detect (low value of area and height). A standard BGE containing 25 mM borax (pH 9.3) was than selected, taking in consideration also previous electrophoretic studies, however the disadvantage in a basic environment was that LET migrated very close to the electroosmotic flow (EOF) [16][17][18][19]. Adding sodium dodecyl sulfate (SDS) in the 25 mM borax BGE did not resolved the problem.…”
Section: A Capillary Zone Electrophoresismentioning
confidence: 99%
“…Until now, on a base of detailed literature survey, it was found that LET could be estimated along with other compounds only by MEKC [16][17][18][19].…”
Section: A Capillary Zone Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation